KINERJA PEGAWAI TATA USAHA DI SMP NEGERI 3 KECAMATAN HUAMUAL KABUPATEN SERAM BAGIAN BARAT - Jumiyati Saun (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This research is a study that uses qualitative methods aimed at analyzing the performance of School Administration employees at SMP Negeri 3, Huamual District, West Seram Regency. This research was conducted at the SMP Negeri 3, Huamual District, West Seram Regency. Primary data collection was conducted through interviews with a number of informants who were directly involved in the employee performance process. The results of this study describe that the quality of performance of School Administration employees at SMP Negeri 3, Huamual District in West Seram Regency is generally categorized as not good, this is evidenced by the main tasks of the school administration which are not carried out optimally because the facilities / infrastructure at SMP Negeri 3, Huamual District, West Seram Regency are not adequate so that it affects employee performance.